2017
DOI: 10.1097/psy.0000000000000456
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Influences on Sleep, Pain, and Depression Symptoms in a Community Sample of Twins

Abstract: Objective We used quantitative genetic methods to evaluate whether sleep quality, pain, and depression symptoms share a common genetic diathesis, to estimate the genetic and environmental sources of covariance among these symptoms, and to test for possible causal relationships. Methods A community sample of 400 twins from the University of Washington Twin Registry completed standardized self-report questionnaires. We used biometric modeling to assess genetic and environmental contribution to the association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
27
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 48 publications
9
27
3
Order By: Relevance
“…These traits are known to often co-occur with BP and twin studies have suggested that they share underlying genetic factors 17 , with similar genetic correlations also seen for other pain phenotypes. [55][56][57] Our results confirm a recent twin report of genetic correlation of sleep disturbance with BP. 58 Overall, the analysis of genetic correlations provides evidence for shared molecular pathways underlying BP and traits considered as BP risk factors, thus providing basis for identification of causal links between them.…”
Section: Discussionsupporting
confidence: 90%
“…These traits are known to often co-occur with BP and twin studies have suggested that they share underlying genetic factors 17 , with similar genetic correlations also seen for other pain phenotypes. [55][56][57] Our results confirm a recent twin report of genetic correlation of sleep disturbance with BP. 58 Overall, the analysis of genetic correlations provides evidence for shared molecular pathways underlying BP and traits considered as BP risk factors, thus providing basis for identification of causal links between them.…”
Section: Discussionsupporting
confidence: 90%
“…When norm estimates from the nonclinical sample of the original psychometric study of the BSI were used (Derogatis & Melisaratos, 1983), this proportion was estimated to be 21.6%. However, it should be noted that the mean scores of the nonclinical sample in the original psychometric study were substantially lower than those reported by subsequent studies from the United States and Western Europe (e.g., Gasperi, Herbert, Schur, Buchwald, & Afari, 2017;Rytilä-Manninen et al, 2016). The latter estimate of 21.6%, therefore, is likely to be too high.…”
Section: Discussionmentioning
confidence: 61%
“…Pain was present in around 65% in depressed patients and up to 85% of patients with chronic pain were affected by severe depression [32]. Previous studies have reported a genetic correlation between pain and depression of 0.56 (in a sample of twins) and 0.51 (in a family-based samples) [19,33]. Although the exact mechanisms linking these conditions are not clear, genetic mechanisms are implied through shared biological pathways, such as gene expression in biological networks, the endocannabinoid system, the hypothalamic-pituitary-adrenal axis and inflammatory pathways [34].…”
Section: Discussionmentioning
confidence: 99%